FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN CAMPAGO IPUH KOTA BUKITTINGGI TAHUN 2017 - Harisnal Harisnal (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Dengue Hemorrhagic Fever (DHF) is caused by dengue virus transmitted byAedes Aegypti mosquitoes. Based on data from the Bukittinggi City Health Office(DKK) in 2017 as many as 90 cases. This study aims to determine the factors associatedwith the incidence of Dengue Hemorrhagic Fever (DHF) in Campago Ipuh Village,Bukittinggi City in 2017.The type of research used is descriptive analytic with cross sectional design. Thisresearch was carried out by all families in Campago Ipuh Village in 2017 totaling 2636households, the sample was taken systematically random sampling totaling 99 families.By using the chi squere test with a confidence level (CI) 95% (<0.005).The results of univariate analysis (66.7%) had low knowledge, (71.7%)respondents had a negative attitude, (63.6%) respondents who did not carry out the act ofEradicating Mosquito Nests (PSN), (62.6%) respondents who assume that the role of theofficer is less active. Bivariate results showed a significant relationship betweenknowledge with the incidence of DHF (p = 0.007 and OR = 3.61), attitudes with DHFincidence (p = 0.020 and OR = 3.17), PSN actions with DHF incidence (p = 0.002 andOR = 4.11), the role of officers with dengue incidence (p = 0,000 and OR = 0,115).It was concluded that related to the incidence of DHF were knowledge, attitudes,actions of PSN, the role of officers. It is suggested to the public to be more active in thePSN action to avoid the incidence of DHF.Keywords: Dengue Hemorrhagic Fever (DHF), Knowledge, Attitude, PSN Actions, Role ofOfficers Reference: 23 (2005-2017)